"New Biology" and Its Educational Outcomes - Chudinova E.V (Moscow State University of Psychology and Education, 2019)
The paper presents data of a study on the effectiveness of an experimental school course in biology based on the principles of Davydov-Elkonin developmental learning in comparison with traditional courses. The study involved 395 students of 5th, 6th, and 9th classes. The results show that children can be more successful at achieving not only subject, but also metasubject educational outcomes like reading literacy, ability to work with signs, symbols and models etc, which are all required by the federal state education standard, if the content of education is changed in such a way that the integral system of key concepts becomes the subject matter, presented not as a means of describing an object, but rather as a basis for its transformation by students. When learning is organised that way, it provides an opportunity for primary school students with underdeveloped reading skills to compensate for the lack of reading literacy, although it will still be hard for them to master subject concepts successfully enough.